Pergeseran Bentuk Kepemimpinan Profetik Pada Masa Khilafah Hingga Masa Modern Di Indonesia - Agustin, Lusi Tania (Ikhtisar: Jurnal Pengetahuan Islam, 2023)
Prophetic leadership is widely discussed and has concepts up to transcendence. Prophetic that is oriented towards leadership during the time of the Prophet and Khulafaur Rashidin with success scores. Exemplary and justice were felt in the leadership of the prophet and khuafaur rasyidin. Leadership is carried out well because of the clear foundation of Islamic teachings about life. Internally, especially for the Indonesian people. The prophetic leadership model has not been used as the main reference. The values and morals that are created are still limited to textual words. Content that does not necessarily use the Prophet's leadership values as a reference. This is found in various regions in Indonesia itself. In fact, the various problems faced by the Indonesian people are very varied. So it is necessary to study how the form of leadership shifted from the Caliphate period to the Modern period in Indonesia. The aim of this research is to analyze the shift in forms of leadership from the Khilafah period to the Modern period in Indonesia. The research method used in this research is a library approach. Research objects consist of 2, namely formal objects and material objects. The data analysis technique uses a "qualitative" analysis strategy, this strategy means that the analysis starts from the data and leads to general conclusions. The results of this research show that there has been a shift in the form of prophetic leadership from the caliphate period to the modern era in Indonesia, due to political and economic interests.